Infraestrutura virtualizada em laboratórios de computação: novas perspectivas de expansão para o ensino - Diniz Rossi, Fábio (2011)
Virtualization has been on the increase of attention through the past few years. It enables the execution of many independent operational systems on an only operational system. It makes feasible a simulation of an interconnected group of machines, without the cost of an actual structure. Its use eases the system operating and data communication teaching process, since it enables practice in distributed systems using only one computer. For such, open source software were used. Throughout the following paper, an academic experience of the use of these technologies together will be presented; aiming at the practical teaching on the interconnection of devices and computational systems.